2020
DOI: 10.3389/fmicb.2020.01663
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation and Genomics Prove Long-Term Colonization of Donor’s Bifidobacteria in Recurrent Clostridioides difficile Patients Treated With Fecal Microbiota Transplantation

Abstract: Fecal microbiota transplantation (FMT) is an effective treatment for recurrent Clostridioides difficile infection (rCDI) and it's also considered for treating other indications. Metagenomic studies have indicated that commensal donor bacteria may colonize FMT recipients, but cultivation has not been employed to verify strain-level colonization. We combined molecular profiling of Bifidobacterium populations with cultivation, molecular typing, and whole genome sequencing (WGS) to isolate and identify strains tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 58 publications
(83 reference statements)
0
20
0
Order By: Relevance
“…To simplify the influence of FMT on gut microbiota, studies among specific populations, such as groups with malignancy or inflammatory bowel disease, are not discussed in this review [ 16 ]. Since the poor bacterial diversity is correlated with rCDIs in clinical patients, the efficacy of FMT in preventing rCDIs has been correlated with the restoration of the disturbed and poor diversity of gut microbiota due to the disruption by antibiotic exposures [ 17 , 18 ], for example, replanting the genera of Bacteroidetes [ 16 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], Firmicutes [ 23 , 25 ], Faecalibacterium [ 16 , 26 ], or Bifidobacterium [ 27 ], and conveniently decreasing Proteobacteria [ 22 , 25 , 28 ], Enterobacteriaceae [ 29 , 30 ], or bacteria harboring antibiotic-resistant genes within the microbiota [ 25 ].…”
Section: Disruption Of Gut Microbiota After Antibiotic Exposure Results In Recurrent C Difficile Infectionmentioning
confidence: 99%
See 3 more Smart Citations
“…To simplify the influence of FMT on gut microbiota, studies among specific populations, such as groups with malignancy or inflammatory bowel disease, are not discussed in this review [ 16 ]. Since the poor bacterial diversity is correlated with rCDIs in clinical patients, the efficacy of FMT in preventing rCDIs has been correlated with the restoration of the disturbed and poor diversity of gut microbiota due to the disruption by antibiotic exposures [ 17 , 18 ], for example, replanting the genera of Bacteroidetes [ 16 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], Firmicutes [ 23 , 25 ], Faecalibacterium [ 16 , 26 ], or Bifidobacterium [ 27 ], and conveniently decreasing Proteobacteria [ 22 , 25 , 28 ], Enterobacteriaceae [ 29 , 30 ], or bacteria harboring antibiotic-resistant genes within the microbiota [ 25 ].…”
Section: Disruption Of Gut Microbiota After Antibiotic Exposure Results In Recurrent C Difficile Infectionmentioning
confidence: 99%
“…The diverse change in microbiota after FMT was noticed, which might depend on the different composition of microbiota of the donor population, different donor ages, or different FMT methods [ 22 , 23 , 27 , 31 , 32 ]. For all successful FMT treatments with the resolution of rCDI symptoms and a negative C. difficile toxin test within 4–12 weeks after FMT, the genomic analysis of donor microbiota showed that the Bacteroidetes-to-Fermicutes ratio did not reveal a significant difference among donors with different ages [ 32 ].…”
Section: Disruption Of Gut Microbiota After Antibiotic Exposure Results In Recurrent C Difficile Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“… 6 , 8 The potential of different species and strains within the donor´s microbiota to colonize the recipient gut is affected by multiple factors, including the properties of individual strains and co-transferred bacteria as well as the recipient´s endogenous microbiota and niche opportunity in the new ecosystem. 9–12 The key bacterial species associated with a positive outcome upon FMT are yet to be identified.…”
Section: Introductionmentioning
confidence: 99%